KESESUAIAN KEBERADAAN RUMAH TIDAK LAYAK HUNI (RTLH) TERHADAP TATA RUANG WILAYAH DI KOTA YOGYAKARTA - Su Ritohardoyo; Mohammad Isnaini Sadali (Diponegoro University, 2017)
Residence is one of the basic rights of every person, meaning that every citizen has the right to reside and got a decent living environment. But in reality, not everyone can get a place to stay that is livable. This has been, is, and will became always a problem for communities and governments in developing residential areas with proper environmental quality. Therefore, this paper presents the results of research that aims to: (1) identification and mapping out where residence were un-inhabitable (RTLH); (2) analysis of the suitability of the location RTLH the spatial plan; and (3) analysis RTLH handling, to formulate strategies based on spatial policy. The study was conducted in the city of Yogyakarta, is based on a spatial approach using secondary data, data analysis using quantitative and qualitative descriptive methode. The results showed that the number of RTLH in Yogyakarta until the year 2014 as a whole is 3,304 residences, or 3.55 percent of the total number of residences (92 965 pieces), spread over 14 districts and 45 villages. Judging spatial, the majority (65.63%) RTLH is in a residential zone, while others (34.37%) RTLH are in non-residential zone. RTLH in non-residential zone, 13.09 percent are in protected areas, namely in the zone of green open space (RTH) of 9.42 percent, and 3.67 percent in the zones of nature reserves and cultural heritage. The remaining 21.28 percent RTLH contained in non-residential area of cultivation. RTLH handling can be done by way of demolition, relocation, land acquisition, as well as indemnity. RTLH for priority handling should be done in a protected area. Efforts that can be implemented to overcome the problems RTLH and slums, is to provide support for policy and program strategies appropriate, integrated and comprehensive.